Hunted : a house of night novel - Cast, P. C.; Cast, Kristin (Cast, P. C. House of night ;, 2009)
" ... Zoey's friends have her back again and Stevie Rae and the red fledglings aren't Neferet's secrets any longer. But an unexpected danger has emerged. Neferet guards her powerful new consort, Kalona, and no one at the House of Night seems to understand the threat he poses. Kalona looks gorgeous, and he has the House of Night under his spell. A past life holds the key to breaking his rapidly spreading influence, but what if this past life shows Zoey secrets she doesn't want to hear and truths she can't face? On the run and holed up in Tulsa's Prohibition-era tunnels, Zoey and her gang must discover a way to deal with something that might bring them all down ..."--